YOUTH CREATIVE CENTER DI TABALONG DENGAN PENERAPAN FLEKSIBILITAS RUANG - Amelia, Neta; Fawzia, Irma (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2025)
The design of the Youth Creative Center in Tabalong is an effort to realize the development of the creative industry in Tabalong by looking at the nature of innovation that continues to change and increase. Therefore, a flexible space is needed to adapt to these changes. This building design applies flexible architectural methods by using the flex-space concept implemented through three miniconcepts namely, expansibility, convertibility, and versability; and by paying attention to the principles of adaptable, movable, universal, and transformable in a space. Through the application of flexible architecture methods, the concept of flex-space is achieved with adaptability, ease of collaboration and interaction, and optimization of space functions.